Application of SPH to Single and Multiphase Geophysical, Biophysical and Industrial Fluid Flows. Issue 1 (7th February 2021) - Cleary, Paul W.; Harrison, Simon M.; Sinnott, Matt D.; Pereira, Gerald G.; Prakash, Mahesh; Cohen, Raymond C. Z.; Rudman, Murray; Stokes, Nick
Abstract : A series of challenging fluid flow applications are used to demonstrate the powerful capabilities of the SPH method. The applications are classified according to whether they are industrial, geophysical or biophysical in nature. The versatility and flexibility of SPH allows it to be used to predict wide ranges of flow types with diverse coupled secondary physics and chemistry. The demonstration examples span free surface hydrodynamics, fluid-structure interactions, multiphase flows (bubbles and/or solids immersed in a fluid and multiple fluids with large density differences), and flows involving reactions and phase change. For the studies presented SPH demonstrates at least one and often several key advantages that make the method well suited to these applications. These include the natural handling of free surfaces (especially when splashing), strong advection (arising from the method being Lagrangian), very high deformation levels (due to being meshfree) and intrinsic history tracking (which provides specific benefits for flows with multiple materials, reactions and phase change).